Analisis Perilaku Konsumen dan Bauran Pemasaran Terhadap Keputusan Pembelian pada Usaha Kopi Keliling di Kota Bima (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of consumer behavior and marketing mix on purchasing decisions in mobile coffee businesses in Bima City. The research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS 26. The results indicate that consumer behavior has a positive and significant effect on purchasing decisions, with a regression coefficient of 0.519 and a significance value of 0.000. The marketing mix also has a positive and significant effect on purchasing decisions, with a regression coefficient of 0.438 and a significance value of 0.000. Simultaneously, consumer behavior and marketing mix significantly influence purchasing decisions, as indicated by an F-value of 721.347 and a significance level of 0.000. The coefficient of determination (R²) of 0.937 shows that 93.7% of the variation in purchasing decisions can be explained by both variables. These findings suggest that understanding consumer characteristics and implementing an effective marketing mix are essential for increasing consumer purchasing decisions in mobile coffee businesses in Bima City.